Formula and preparation method of long-acting anti-corrosion alloy coating

By adopting a long-term anticorrosion alloy coating formula composed of A/B two-component, the existing anticorrosion alloy coatings have been solved, and the uniform anticorrosion and weather resistance of the coating have been improved, and the protection life has been extended.

CN119592184AInactive Publication Date: 2025-03-11WUXI GANCHAO NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411462041.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing anticorrosion alloy coatings have poor bonding power, poor weather resistance and low anticorrosion efficiency during long-term use, especially in harsh environments that are prone to peeling, aging, cracking and powdering.

Method used

A long-acting anticorrosion alloy coating formula consisting of A/B two components, wherein component A includes polyurethane, aluminum-zinc alloy powder, titanium dioxide, talc powder, defoaming agent, thickening agent and water, and component B is a curing agent, prepared by specific stirring, grinding and centrifugal filtration steps.

Benefits of technology

It achieves uniform corrosion protection of the coating, improves the bonding force and weather resistance between the coating and the substrate, extends the protection life, and has good wear and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of coating preparation, and particularly discloses a long-acting anti-corrosion alloy coating formula and a preparation method thereof. The raw material is composed of a component A and a component B, wherein the component A comprises 30-50 parts of polyurethane, 20-40 parts of aluminum-zinc alloy powder, 5-7 parts of titanium dioxide, 6-8 parts of talcum powder, 1-3 parts of a defoaming agent, 1-3 parts of a thickening agent and 20-40 parts of water; the component B is a curing agent; the preparation method of the long-acting anti-corrosion alloy coating comprises the following steps: S1, stirring and mixing polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, a defoaming agent, a thickening agent and water, and grinding to obtain a mixture; and S2, adding a curing agent into the mixture, stirring and mixing, centrifugally filtering, and grinding to obtain the anti-corrosion alloy coating. By designing the raw materials and the proportion, the prepared anti-corrosion alloy coating has relatively high corrosion resistance, wear resistance and excellent metal substrate adhesive force, and long-acting corrosion resistance can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coating preparation, and more specifically, to a long-lasting anti-corrosion alloy coating formulation and a preparation method thereof. Background Art

[0002] Alloy coating is a high-performance special coating made of a mixture of various materials. It has excellent weather resistance, chemical resistance, high gloss and strong adhesion. It is widely used in many fields such as construction, automobiles, machinery and electronics. The main components of alloy coatings usually include resins, pigments, additives and water. Among them, resin, as the base material of the coating, provides the adhesion and hardness of the coating; pigments give the coating rich colors and hiding power; additives are used to improve the construction performance of the coating and the performance of the final coating; water is used to adjust the viscosity and fluidity of the coating to ensure smooth construction.

[0003] Anti-corrosion alloy coatings, as a special type of coating, are designed to form a protective layer on the metal surface to resist the erosion of various corrosion factors, thereby extending the service life of the metal. In the existing technology, anti-corrosion alloy coatings still have the following defects: 1) Since the bonding force between the anti-corrosion alloy coating and the metal substrate is not strong enough, the coating is easy to peel off or peel off during long-term use, thus losing the anti-corrosion effect; 2) Under harsh environmental conditions, such as high temperature, high humidity, and strong corrosive media, the coating has insufficient adhesion; 3) In outdoor environments, it is easily affected by natural factors such as ultraviolet rays, wind and rain, and temperature changes, and has poor weather resistance, resulting in aging, cracking, and powdering of the coating. Summary of the invention

[0004] In order to solve the problems of poor bonding, poor weather resistance and low anti-corrosion performance of anti-corrosion alloy coatings in related technologies, the present application provides a long-lasting anti-corrosion alloy coating formula and a preparation method thereof.

[0005] The present application proposes a long-lasting anti-corrosion alloy coating, the raw materials of which are composed of a two-component A / B. Component A includes the following raw materials in parts by weight: 30-50 parts of polyurethane, 20-40 parts of aluminum-zinc alloy powder, 5-7 parts of titanium dioxide, 6-8 parts of talcum powder, 1-3 parts of defoaming agent, 1-3 parts of thickener and 20-40 parts of water; component B: curing agent.

[0006] Preferably, the mass ratio of component A to component B is 4-6:1.

[0007] Preferably, the aluminum-zinc alloy powder comprises the following components by weight percentage: 8.5-10.5% zinc, 0.2-0.4% magnesium, 0.1-0.3% iron, 0.05-0.25% rare earth elements, and the balance is aluminum.

[0008] Preferably, the preparation method of the aluminum-zinc alloy powder is as follows: (1) Mix zinc, magnesium, iron and aluminum raw materials according to the component ratio, cool them down after smelting, and keep the melt temperature at 760℃-780℃; (2) adding rare earth elements to the melt, stirring the alloy melt to obtain a uniform aluminum-zinc alloy melt, and removing slag at the same time; (3) The aluminum-zinc alloy melt is poured into a mold and cooled and solidified into an aluminum-zinc alloy ingot, which is then ground to obtain an aluminum-zinc alloy powder.

[0009] Preferably, the rare earth element is at least one of lanthanum, cerium and praseodymium.

[0010] Preferably, the defoaming agent is AFE-0050.

[0011] Preferably, the thickener is a mixture of methyl cellulose and hydroxyethyl cellulose in a mass ratio of 2-4:1-3.

[0012] Preferably, the curing agent is at least one of triethylenetetramine, polysilicic acid ester and hexamethylenetetramine.

[0013] Preferably, the curing agent is composed of triethylenetetramine, polysilicic acid ester and hexamethylenetetramine mixed in a mass ratio of 1:1-3:0.5-2.5.

[0014] The present application also proposes a method for preparing a long-lasting anti-corrosion alloy coating, comprising the following steps: S1, mixing polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, defoamer, thickener and water, and grinding to obtain a mixture; S2. Add a curing agent to the mixture, stir and mix, centrifuge and filter, and grind to obtain an anti-corrosion alloy coating.

[0015] In summary, this application has the following beneficial effects: 1. The present application uses a coating prepared from an aluminum-zinc alloy, and the components in the coating are evenly distributed, thereby achieving uniform corrosion protection. When the coating is scratched or partially defective, or when the corrosive medium reaches the substrate, the coating and the substrate form a corrosion protection layer. The coating acts as a sacrificial anode to protect the steel substrate from corrosion, and has a good cathodic protection effect of a sacrificial anode, thereby giving full play to the corrosion protection performance of the alloy coating.

[0016] 2. The corrosion current density of the coating prepared by the aluminum-zinc alloy in this application is small, indicating that the corrosion rate of the coating is low, thereby extending the protective life. At the same time, the aluminum-zinc alloy coating has a high hardness, high hardness and high wear resistance, and the coating is not easily damaged. Therefore, the aluminum-zinc alloy coating has good wear resistance and corrosion resistance.

[0017] 3. The present application adds the rare earth element cerium (Ce) during the preparation process of aluminum-zinc alloy, which can not only significantly improve the refining effect of the alloy, reduce impurities and defects in the alloy, thereby enhancing the purity and performance of the material. It can also significantly improve the mechanical properties of zinc-aluminum alloys, such as strength, hardness, ductility and impact toughness, which helps to improve the stability and durability of the material in various application environments. In some harsh environmental conditions, such as high temperature, high humidity or environments containing corrosive media, zinc-aluminum alloys with the addition of rare earth cerium have better corrosion resistance. In addition, rare earth cerium can also be used as a microalloying element to react with other elements such as zinc and aluminum to form stable compounds or phase structures, thereby improving the physical and chemical properties of the alloy. DETAILED DESCRIPTION

[0018] The present application is further described in detail below with reference to the embodiments.

[0019] Examples 1-5 provide a long-lasting anti-corrosion alloy coating formulation and a preparation method thereof.

[0020] Example 1 A long-lasting anti-corrosion alloy coating, whose raw materials are composed of two components A / B in a mass ratio of 4:1, component A includes 30 parts of polyurethane, 20 parts of aluminum-zinc alloy powder, 5 parts of titanium dioxide, 6 parts of talcum powder, 1 part of defoaming agent, 1 part of thickener and 20 parts of water; component B is a curing agent.

[0021] The preparation method of the aluminum-zinc alloy powder is as follows: (1) Weigh 8.5% zinc, 0.2% magnesium, 0.1% iron, 0.05% cerium and the balance aluminum according to weight percentage; mix the zinc, magnesium, iron and aluminum raw materials, smelt for 1 hour and then cool to 760°C; (2) Add cerium to the melt, stir at 400 r / min for 30 min, continue smelting, control the smelting temperature to 720 ° C, the smelting time to 1 h, and remove the slag at the same time; (3) The aluminum-zinc alloy melt is poured into a mold and cooled and solidified into an aluminum-zinc alloy ingot, and the ingot is ground to 50 microns to obtain an aluminum-zinc alloy powder.

[0022] A method for preparing a long-lasting anti-corrosion alloy coating comprises the following steps: S1, mixing polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, defoamer, thickener and water at a speed of 400 r / min for 1 h, and grinding to a fineness of 30 μm to obtain a mixture; S2. Add curing agent to the mixture, stir and mix at a speed of 600 r / min for 20 minutes, centrifuge and filter, control the centrifugal speed to 10000 r / min, the centrifugal time to 10 minutes, and then grind to a fineness of 10 microns to obtain an anti-corrosion alloy coating.

[0023] Among them, the polyurethane described in step S1 is selected from the polyurethane TPU raw material 385E of Covestro of Germany; the titanium dioxide is selected from the rutile titanium dioxide LR-972 of Longbai; the talc powder is selected from the talc powder CB-3000 mesh of Hongyunyuan; the defoaming agent is AFE-0050; and the thickener is composed of methyl cellulose and hydroxyethyl cellulose mixed in a mass ratio of 2:1.

[0024] The curing agent in step S2 is composed of triethylenetetramine, polysilicic acid ester and hexamethylenetetramine mixed in a mass ratio of 1:1:0.5.

[0025] Example 2 A long-lasting anti-corrosion alloy coating, whose raw materials are composed of two components A / B in a mass ratio of 4.5:1, component A includes 35 parts of polyurethane, 25 parts of aluminum-zinc alloy powder, 5.5 parts of titanium dioxide, 6.5 parts of talcum powder, 1.5 parts of defoaming agent, 1.5 parts of thickener and 25 parts of water; component B is a curing agent.

[0026] The preparation method of the aluminum-zinc alloy powder is as follows: (1) Weigh 9% zinc, 0.25% magnesium, 0.15% iron, 0.1% cerium, and the balance aluminum according to weight percentage; mix the zinc, magnesium, iron, and aluminum raw materials, smelt for 1.5 hours, and then cool to 765°C; (2) Add cerium to the melt, stir at 450 r / min for 35 min, continue smelting, control the smelting temperature to 725 ° C, the smelting time to 1.5 h, and remove the slag at the same time; (3) The aluminum-zinc alloy melt is poured into a mold and cooled and solidified into an aluminum-zinc alloy ingot, and the ingot is ground to 55 microns to obtain an aluminum-zinc alloy powder.

[0027] A method for preparing a long-lasting anti-corrosion alloy coating comprises the following steps: S1, mixing polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, defoamer, thickener and water at a speed of 450 r / min for 1.5 h, and grinding to a fineness of 35 μm to obtain a mixture; S2. Add curing agent to the mixture, stir and mix at a speed of 650 r / min for 25 minutes, centrifuge and filter, control the centrifugal speed to 10500 r / min, the centrifugal time to 15 minutes, and then grind to a fineness of 15 microns to obtain an anti-corrosion alloy coating.

[0028] Among them, the polyurethane described in step S1 is selected from the polyurethane TPU raw material 385E of Covestro of Germany; the titanium dioxide is selected from the rutile titanium dioxide LR-972 of Longbai; the talc powder is selected from the talc powder CB-3000 mesh of Hongyunyuan; the defoaming agent is AFE-0050; the thickener is composed of methyl cellulose and hydroxyethyl cellulose mixed in a mass ratio of 2..5:1.5.

[0029] The curing agent in step S2 is composed of triethylenetetramine, polysilicic acid ester and hexamethylenetetramine mixed in a mass ratio of 1:1.5:1.

[0030] Example 3 A long-lasting anti-corrosion alloy coating, whose raw materials are composed of two components A / B in a mass ratio of 5:1, component A includes 40 parts of polyurethane, 30 parts of aluminum-zinc alloy powder, 6 parts of titanium dioxide, 7 parts of talcum powder, 2 parts of defoaming agent, 2 parts of thickener and 30 parts of water; component B is a curing agent.

[0031] The preparation method of the aluminum-zinc alloy powder is as follows: (1) Weigh 9.5% zinc, 0.3% magnesium, 0.2% iron, 0.15% cerium and the balance aluminum according to weight percentage, mix the zinc, magnesium, iron and aluminum raw materials, smelt for 2 hours and then cool to 770°C; (2) Add cerium to the melt, stir at 500 r / min for 40 min, continue smelting, control the smelting temperature to 730 ° C, the smelting time to 2 h, and remove the slag at the same time; (3) The aluminum-zinc alloy melt is poured into a mold and cooled and solidified into an aluminum-zinc alloy ingot, and the ingot is ground to 60 microns to obtain an aluminum-zinc alloy powder.

[0032] A method for preparing a long-lasting anti-corrosion alloy coating comprises the following steps: S1, mixing polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, defoamer, thickener and water at a speed of 500 r / min for 2 h, and grinding to a fineness of 40 μm to obtain a mixture; S2. Add curing agent to the mixture, stir and mix at a speed of 700 r / min for 30 minutes, centrifuge and filter, control the centrifugal speed to 11000 r / min, the centrifugal time to 20 minutes, and then grind to a fineness of 20 microns to obtain an anti-corrosion alloy coating.

[0033] Among them, the polyurethane described in step S1 is selected from the polyurethane TPU raw material 385E of Covestro of Germany; the titanium dioxide is selected from the rutile titanium dioxide LR-972 of Longbai; the talc powder is selected from the talc powder CB-3000 mesh of Hongyunyuan; the defoaming agent is AFE-0050; and the thickener is composed of methyl cellulose and hydroxyethyl cellulose mixed in a mass ratio of 3:2.

[0034] The curing agent in step S2 is composed of triethylenetetramine, polysilicic acid ester and hexamethylenetetramine mixed in a mass ratio of 1:2:1.5.

[0035] Example 4 A long-lasting anti-corrosion alloy coating, whose raw materials are composed of two components A / B in a mass ratio of 5.5:1, component A includes 45 parts of polyurethane, 35 parts of aluminum-zinc alloy powder, 6.5 parts of titanium dioxide, 7.5 parts of talcum powder, 2.5 parts of defoaming agent, 2.5 parts of thickener and 35 parts of water; component B is a curing agent.

[0036] The preparation method of the aluminum-zinc alloy powder is as follows: (1) Weigh the raw materials of zinc (10%), magnesium (0.35%), iron (0.25%), cerium (0.2%) and aluminum (the remainder) by weight, mix the zinc, magnesium, iron and aluminum raw materials, smelt for 2.5 hours and then cool to 775°C; (2) Add cerium to the melt, stir at 550 r / min for 45 min, continue smelting, control the smelting temperature to 735 ° C, the smelting time to 2.5 h, and remove the slag at the same time; (3) The aluminum-zinc alloy melt is poured into a mold and cooled and solidified into an aluminum-zinc alloy ingot, and the ingot is ground to 65 microns to obtain an aluminum-zinc alloy powder.

[0037] A method for preparing a long-lasting anti-corrosion alloy coating comprises the following steps: S1. Mix polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, defoamer, thickener and water at a speed of 550 r / min for 2.5 h, and grind to a fineness of 45 μm to obtain a mixture; S2. Add curing agent to the mixture, stir and mix at a speed of 750 r / min for 35 minutes, centrifuge and filter, control the centrifugal speed to 11500 r / min, the centrifugal time to 25 minutes, and then grind to a fineness of 25 microns to obtain an anti-corrosion alloy coating.

[0038] Among them, the polyurethane described in step S1 is selected from the polyurethane TPU raw material 385E of Covestro of Germany; the titanium dioxide is selected from the rutile titanium dioxide LR-972 of Longbai; the talc powder is selected from the talc powder CB-3000 mesh of Hongyunyuan; the defoaming agent is AFE-0050; the thickener is composed of methyl cellulose and hydroxyethyl cellulose mixed in a mass ratio of 3.5:2.5.

[0039] The curing agent in step S2 is composed of triethylenetetramine, polysilicic acid ester and hexamethylenetetramine mixed in a mass ratio of 1:2.5:2.

[0040] Example 5 A long-lasting anti-corrosion alloy coating, whose raw materials are composed of two components A / B in a mass ratio of 6:1, component A includes 50 parts of polyurethane, 40 parts of aluminum-zinc alloy powder, 7 parts of titanium dioxide, 8 parts of talcum powder, 3 parts of defoaming agent, 3 parts of thickener and 40 parts of water; component B is a curing agent.

[0041] The preparation method of the aluminum-zinc alloy powder is as follows: (1) Weigh the raw materials of zinc 10.5%, magnesium 0.4%, iron 0.3%, cerium 0.25%, and the balance aluminum by weight, mix the zinc, magnesium, iron and aluminum raw materials, smelt for 3 hours, and then cool to 780°C; (2) Add cerium to the melt, stir at 600 r / min for 50 min, continue smelting, control the smelting temperature to 740 ° C, the smelting time to 3 h, and remove the slag at the same time; (3) The aluminum-zinc alloy melt is poured into a mold and cooled and solidified into an aluminum-zinc alloy ingot, and the ingot is ground to 70 microns to obtain an aluminum-zinc alloy powder.

[0042] A method for preparing a long-lasting anti-corrosion alloy coating comprises the following steps: S1, mixing polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, defoamer, thickener and water at a speed of 600 r / min for 3 hours, and grinding to a fineness of 50 microns to obtain a mixture; S2. Add curing agent to the mixture, stir and mix at a speed of 800 r / min for 40 minutes, centrifuge and filter, control the centrifugal speed to 12000 r / min, the centrifugal time to 30 minutes, and then grind to a fineness of 30 microns to obtain an anti-corrosion alloy coating.

[0043] Among them, the polyurethane described in step S1 is selected from the polyurethane TPU raw material 385E of Covestro of Germany; the titanium dioxide is selected from the rutile titanium dioxide LR-972 of Longbai; the talc powder is selected from the talc powder CB-3000 mesh of Hongyunyuan; the defoaming agent is AFE-0050; and the thickener is composed of methyl cellulose and hydroxyethyl cellulose mixed in a mass ratio of 4:3.

[0044] Step S2: The curing agent is composed of triethylenetetramine, polysilicic acid ester and hexamethylenetetramine mixed in a mass ratio of 1:3:2.5.

[0045] Comparative Example 1 A long-lasting anti-corrosion alloy coating, whose raw materials are composed of two components A / B in a mass ratio of 4:1, component A includes 30 parts of polyurethane, 20 parts of aluminum-zinc alloy powder, 5 parts of titanium dioxide, 6 parts of talcum powder, 1 part of defoaming agent, 1 part of thickener and 20 parts of water; component B is a curing agent.

[0046] The preparation method of the aluminum-zinc alloy powder is as follows: (1) Weigh 8.5% zinc, 0.2% magnesium, 0.1% iron, 0.05% cerium and the balance aluminum according to weight percentage; mix the zinc, magnesium, iron and aluminum raw materials, smelt for 1 hour and then cool to 760°C; (2) Add cerium to the melt, stir at 400 r / min for 30 min, continue smelting, control the smelting temperature to 720 ° C, the smelting time to 1 h, and remove the slag at the same time; (3) The aluminum-zinc alloy melt is poured into a mold and cooled and solidified into an aluminum-zinc alloy ingot, and the ingot is ground to 50 microns to obtain an aluminum-zinc alloy powder.

[0047] A method for preparing a long-lasting anti-corrosion alloy coating comprises the following steps: S1, mixing polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, defoamer, thickener and water at a speed of 400 r / min for 1 h, and grinding to a fineness of 30 μm to obtain a mixture; S2. Add curing agent to the mixture, stir and mix at a speed of 600 r / min for 20 minutes, centrifuge and filter, control the centrifugal speed to 10000 r / min, the centrifugal time to 10 minutes, and then grind to a fineness of 10 microns to obtain an anti-corrosion alloy coating.

[0048] Among them, the polyurethane described in step S1 is selected from the polyurethane TPU raw material 385E of Covestro of Germany; the titanium dioxide is selected from the rutile titanium dioxide LR-972 of Longbai; the talc powder is selected from the talc powder CB-3000 mesh of Hongyunyuan; the defoaming agent is AFE-0050; and the thickener is composed of methyl cellulose and hydroxyethyl cellulose mixed in a mass ratio of 2:1.

[0049] The curing agent in step S2 is composed of triethylenetetramine and polysilicic acid ester mixed in a mass ratio of 1:1.

[0050] Comparative Example 2 A long-lasting anti-corrosion alloy coating, whose raw materials are composed of two components A / B in a mass ratio of 4:1, component A includes 30 parts of polyurethane, 20 parts of aluminum-zinc alloy powder, 5 parts of titanium dioxide, 6 parts of talcum powder, 1 part of defoaming agent, 1 part of thickener and 20 parts of water; component B is a curing agent.

[0051] The preparation method of the aluminum-zinc alloy powder is as follows: (1) Weigh 8.5% zinc, 0.2% magnesium, 0.1% iron, 0.05% cerium and the balance aluminum according to weight percentage; mix the zinc, magnesium, iron and aluminum raw materials, smelt for 1 hour and then cool to 760°C; (2) Add cerium to the melt, stir at 400 r / min for 30 min, continue smelting, control the smelting temperature to 720 ° C, the smelting time to 1 h, and remove the slag at the same time; (3) The aluminum-zinc alloy melt is poured into a mold and cooled and solidified into an aluminum-zinc alloy ingot, and the ingot is ground to 50 microns to obtain an aluminum-zinc alloy powder.

[0052] A method for preparing a long-lasting anti-corrosion alloy coating comprises the following steps: S1, mixing polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, defoamer, thickener and water at a speed of 400 r / min for 1 h, and grinding to a fineness of 30 μm to obtain a mixture; S2. Add curing agent to the mixture, stir and mix at a speed of 600 r / min for 20 minutes, centrifuge and filter, control the centrifugal speed to 10000 r / min, the centrifugal time to 10 minutes, and then grind to a fineness of 10 microns to obtain an anti-corrosion alloy coating.

[0053] Among them, the polyurethane described in step S1 is selected from the polyurethane TPU raw material 385E of Covestro of Germany; the titanium dioxide is selected from the rutile titanium dioxide LR-972 of Longbai; the talc powder is selected from the talc powder CB-3000 mesh of Hongyunyuan; the defoaming agent is AFE-0050; and the thickener is composed of methyl cellulose and hydroxyethyl cellulose mixed in a mass ratio of 2:1.

[0054] The curing agent in step S2 is composed of triethylenetetramine and hexamethylenetetramine mixed in a mass ratio of 1:0.5.

[0055] Comparative Example 3 A long-lasting anti-corrosion alloy coating, whose raw materials are composed of two components A / B in a mass ratio of 4:1, component A includes 30 parts of polyurethane, 20 parts of aluminum-zinc alloy powder, 5 parts of titanium dioxide, 6 parts of talcum powder, 1 part of defoaming agent, 1 part of thickener and 20 parts of water; component B is a curing agent.

[0056] The preparation method of the aluminum-zinc alloy powder is as follows: (1) Weigh 8.5% zinc, 0.2% magnesium, 0.1% iron, 0.05% cerium and the balance aluminum according to weight percentage; mix the zinc, magnesium, iron and aluminum raw materials, smelt for 1 hour and then cool to 760°C; (2) Add cerium to the melt, stir at 400 r / min for 30 min, continue smelting, control the smelting temperature to 720 ° C, the smelting time to 1 h, and remove the slag at the same time; (3) The aluminum-zinc alloy melt is poured into a mold and cooled and solidified into an aluminum-zinc alloy ingot, and the ingot is ground to 50 microns to obtain an aluminum-zinc alloy powder.

[0057] A method for preparing a long-lasting anti-corrosion alloy coating comprises the following steps: S1, mixing polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, defoamer, thickener and water at a speed of 400 r / min for 1 h, and grinding to a fineness of 30 μm to obtain a mixture; S2. Add curing agent to the mixture, stir and mix at a speed of 600 r / min for 20 minutes, centrifuge and filter, control the centrifugal speed to 10000 r / min, the centrifugal time to 10 minutes, and then grind to a fineness of 10 microns to obtain an anti-corrosion alloy coating.

[0058] Among them, the polyurethane described in step S1 is selected from the polyurethane TPU raw material 385E of Covestro of Germany; the titanium dioxide is selected from the rutile titanium dioxide LR-972 of Longbai; the talc powder is selected from the talc powder CB-3000 mesh of Hongyunyuan; the defoaming agent is AFE-0050; and the thickener is methyl cellulose.

[0059] The curing agent in step S2 is composed of triethylenetetramine, polysilicic acid ester and hexamethylenetetramine mixed in a mass ratio of 1:1:0.5.

[0060] Comparative Example 4 A long-lasting anti-corrosion alloy coating, whose raw materials are composed of two components A / B in a mass ratio of 4:1, component A includes 30 parts of polyurethane, 20 parts of aluminum-zinc alloy powder, 5 parts of titanium dioxide, 6 parts of talcum powder, 1 part of defoaming agent, 1 part of thickener and 20 parts of water; component B is a curing agent.

[0061] The preparation method of the aluminum-zinc alloy powder is as follows: (1) Weigh 8.5% zinc, 0.2% magnesium, 0.1% iron, 0.05% cerium and the balance aluminum according to weight percentage; mix the zinc, magnesium, iron and aluminum raw materials, smelt for 1 hour and then cool to 760°C; (2) Add cerium to the melt, stir at 400 r / min for 30 min, continue smelting, control the smelting temperature to 720 ° C, the smelting time to 1 h, and remove the slag at the same time; (3) The aluminum-zinc alloy melt is poured into a mold and cooled and solidified into an aluminum-zinc alloy ingot, and the ingot is ground to 50 microns to obtain an aluminum-zinc alloy powder.

[0062] A method for preparing a long-lasting anti-corrosion alloy coating comprises the following steps: S1, mixing polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, defoamer, thickener and water at a speed of 400 r / min for 1 h, and grinding to a fineness of 30 μm to obtain a mixture; S2. Add curing agent to the mixture, stir and mix at a speed of 600 r / min for 20 minutes, centrifuge and filter, control the centrifugal speed to 10000 r / min, the centrifugal time to 10 minutes, and then grind to a fineness of 10 microns to obtain an anti-corrosion alloy coating.

[0063] Among them, the polyurethane described in step S1 is selected from the polyurethane TPU raw material 385E of Covestro of Germany; the titanium dioxide is selected from the rutile titanium dioxide LR-972 of Longbai; the talc powder is selected from the talc powder CB-3000 mesh of Hongyunyuan; the defoaming agent is AFE-0050; and the thickener is hydroxyethyl cellulose.

[0064] The curing agent in step S2 is composed of triethylenetetramine, polysilicic acid ester and hexamethylenetetramine mixed in a mass ratio of 1:1:0.5.

[0065] Comparative Example 5 A long-lasting anti-corrosion alloy coating, whose raw materials are composed of two components A / B in a mass ratio of 4:1, component A includes 30 parts of polyurethane, 20 parts of aluminum-zinc alloy powder, 5 parts of titanium dioxide, 6 parts of talcum powder, 1 part of defoaming agent, 1 part of thickener and 20 parts of water; component B is a curing agent.

[0066] The preparation method of the aluminum-zinc alloy powder is as follows: weigh 8.5% zinc, 0.05% cerium and the balance aluminum in weight percentage, mix aluminum powder, zinc powder and cerium element, and stir at 400 r / min for 30 minutes to obtain the aluminum-zinc alloy powder.

[0067] A method for preparing a long-lasting anti-corrosion alloy coating comprises the following steps: S1, mixing polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, defoamer, thickener and water at a speed of 400 r / min for 1 h, and grinding to a fineness of 30 μm to obtain a mixture; S2. Add curing agent to the mixture, stir and mix at a speed of 600 r / min for 20 minutes, centrifuge and filter, control the centrifugal speed to 10000 r / min, the centrifugal time to 10 minutes, and then grind to a fineness of 10 microns to obtain an anti-corrosion alloy coating.

[0068] Among them, the polyurethane described in step S1 is selected from the polyurethane TPU raw material 385E of Covestro of Germany; the titanium dioxide is selected from the rutile titanium dioxide LR-972 of Longbai; the talc powder is selected from the talc powder CB-3000 mesh of Hongyunyuan; the defoaming agent is AFE-0050; and the thickener is composed of methyl cellulose and hydroxyethyl cellulose mixed in a mass ratio of 2:1.

[0069] The curing agent in step S2 is composed of triethylenetetramine, polysilicic acid ester and hexamethylenetetramine mixed in a mass ratio of 1:1:0.5.

[0070] Comparative Example 6 A long-lasting anti-corrosion alloy coating, whose raw materials are composed of two components A / B in a mass ratio of 4:1, component A includes 30 parts of polyurethane, 20 parts of aluminum-zinc alloy powder, 5 parts of titanium dioxide, 6 parts of talcum powder, 1 part of defoaming agent, 1 part of thickener and 20 parts of water; component B is a curing agent.

[0071] The preparation method of the aluminum-zinc alloy powder is as follows: (1) Weigh 8.5% zinc, 0.2% magnesium, 0.1% iron and the balance aluminum as raw materials by weight; mix the zinc, magnesium, iron and aluminum raw materials, smelt for 1 hour, then cool to 760°C, stir at 400 r / min for 30 minutes, continue smelting, control the smelting temperature to 720°C, the smelting time is 1 hour, and slag is removed at the same time; (2) Pour the aluminum-zinc alloy melt into a mold, cool and solidify it into an aluminum-zinc alloy ingot; grind the ingot to 50 microns to obtain aluminum-zinc alloy powder.

[0072] A method for preparing a long-lasting anti-corrosion alloy coating comprises the following steps: S1, mixing polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, defoamer, thickener and water at a speed of 400 r / min for 1 h, and grinding to a fineness of 30 μm to obtain a mixture; S2. Add curing agent to the mixture, stir and mix at a speed of 600 r / min for 20 minutes, centrifuge and filter, control the centrifugal speed to 10000 r / min, the centrifugal time to 10 minutes, and then grind to a fineness of 10 microns to obtain an anti-corrosion alloy coating.

[0073] Among them, the polyurethane described in step S1 is selected from the polyurethane TPU raw material 385E of Covestro of Germany; the titanium dioxide is selected from the rutile titanium dioxide LR-972 of Longbai; the talc powder is selected from the talc powder CB-3000 mesh of Hongyunyuan; the defoaming agent is AFE-0050; and the thickener is composed of methyl cellulose and hydroxyethyl cellulose mixed in a mass ratio of 2:1.

[0074] The curing agent in step S2 is composed of triethylenetetramine, polysilicic acid ester and hexamethylenetetramine mixed in a mass ratio of 1:1:0.5.

[0075] Performance Testing The long-lasting anti-corrosion alloy coatings prepared in Examples 1-5 of the present application and Comparative Examples 1-6 were sprayed onto the steel structure base surface respectively, and the comprehensive performance of the coatings was tested.

[0076] 1. Neutral salt spray resistance test According to the standard GB / T 1771-2007, the salt spray resistance of the long-lasting anti-corrosion alloy coatings prepared in Examples 1-5 and Comparative Examples 1-6 was measured. The measurement results are shown in Table 1.

[0077] 2. Adhesion test According to the standard GB / 5210-2006, the adhesion of the long-lasting anti-corrosion alloy coatings prepared in Examples 1-5 and Comparative Examples 1-6 to the steel substrate was measured. The measurement results are shown in Table 1.

[0078] 3. Hardness measurement According to the standard GB / 6379-2006, the hardness of the long-lasting anti-corrosion alloy coatings prepared in Examples 1-5 and Comparative Examples 1-6 was measured. The measurement results are shown in Table 1.

[0079] 4. Impact resistance test According to the standard GB / T1732-2020, the impact resistance of the long-lasting anti-corrosion alloy coatings prepared in Examples 1-5 and Comparative Examples 1-6 was measured, and the measurement results are shown in Table 1.

[0080] Table 1

[0081] It can be seen from the data in Table 1 that compared with Comparative Examples 1-6, the test results of the long-lasting anti-corrosion alloy coating prepared in Examples 1-6 are worse than those in Examples 1-5. The long-lasting anti-corrosion alloy coating prepared in Examples 1-5 is sprayed onto the steel structure base surface and shows stronger salt spray resistance, adhesion, impact resistance and high hardness, indicating that the long-lasting anti-corrosion alloy coating prepared in this application has excellent corrosion resistance, wear resistance and scratch resistance.

[0082] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A long-lasting anti-corrosion alloy coating, characterized in that: The raw materials are composed of two components A / B. Component A includes the following raw materials in parts by weight: 30-50 parts of polyurethane, 20-40 parts of aluminum-zinc alloy powder, 5-7 parts of titanium dioxide, 6-8 parts of talcum powder, 1-3 parts of defoaming agent, 1-3 parts of thickener and 20-40 parts of water; component B: curing agent.

2. The long-lasting anti-corrosion alloy coating according to claim 1, characterized in that: The mass ratio of component A to component B is 4-6:

1.

3. The long-lasting anti-corrosion alloy coating according to claim 1, characterized in that: The aluminum-zinc alloy powder comprises the following components by weight percentage: 8.5-10.5% zinc, 0.2-0.4% magnesium, 0.1-0.3% iron, 0.05-0.25% rare earth element, and the balance is aluminum.

4. The long-lasting anti-corrosion alloy coating according to claim 3, characterized in that: The preparation method of the aluminum-zinc alloy powder is as follows: (1) Mix zinc, magnesium, iron and aluminum raw materials according to the component ratio, cool them down after smelting, and keep the melt temperature at 760℃-780℃; (2) adding rare earth elements to the melt, stirring the alloy melt to obtain a uniform aluminum-zinc alloy melt, and removing slag at the same time; (3) The aluminum-zinc alloy melt is poured into a mold and cooled and solidified into an aluminum-zinc alloy ingot, which is then ground to obtain an aluminum-zinc alloy powder.

5. The long-lasting anti-corrosion alloy coating according to claim 3, characterized in that: The rare earth element is at least one of lanthanum, cerium and praseodymium.

6. The long-lasting anti-corrosion alloy coating according to claim 1, characterized in that: The thickener is composed of methyl cellulose and hydroxyethyl cellulose mixed in a mass ratio of 2-4:1-3.

7. The long-lasting anti-corrosion alloy coating according to claim 1, characterized in that: The curing agent is at least one of triethylenetetramine, polysilicic acid ester and hexamethylenetetramine.

8. A long-lasting anti-corrosion alloy coating according to any one of claims 1 to 7, characterized in that: The preparation method of the long-lasting anti-corrosion alloy coating comprises the following steps: S1, mixing polyurethane, aluminum-zinc alloy powder, titanium dioxide, talcum powder, defoamer, thickener and water, and grinding to obtain a mixture; S2. Add a curing agent to the mixture, stir and mix, centrifuge and filter, and grind to obtain an anti-corrosion alloy coating.